Eglise-de-Bellevue - Guy Courtois (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: Eglise-de-Bellevue. Scan of an old postcard of the Bellevue Church in Meudon (France)
Droits : Licence Creative Commons Attribution-Share Alike 3.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale